Physical Inactivity, Obesity, and Type 2 Diabetes: An Evolutionary Perspective - Eaton, S. Boyd; Eaton, Stanley B. (Research quarterly for exercise and sport, 2017)
Physical inactivity (and unhealthy nutrition) has distorted body composition and, in turn, reordered the proportions of myocyte and adipocyte insulin receptors. Insulin acting on adipocyte receptors produces less glucose uptake than does comparable interaction with myocyte receptors. Accordingly, in individuals with disproportionate muscle/fat composition, any given glucose load requires greater-than-normal pancreatic insulin secretion for adequate disposal. This hyperinsulinemia then becomes the leading cause of type 2 diabetes (T2DM) as insulin-sensitive tissues become desensitized. Because T2DM is rooted in potentially reversible lifestyle factors, rather than focusing on the intricacies of glucoregulation at the molecular level and on testing new drugs to control blood sugar, this article calls for a new prevention and treatment paradigm, in which exercise and weight control are essential and for which an inexpensive and acceptably accurate measure of body muscle and fat proportions is needed.